A Bibliometric Analysis on Transformational Leadership - Malodia, Luxmi; Arora, Sudiksha (Gyan Management Journal, 2024)
This paper reveals the literature on transformational leadership. The study focuses on gathering the information related to the transformational leaders. The data was collected from 6,090 papers published from 2012 to 2022. The search items considered the following keywords: “transformational leadership”, “transformational leader”, “transform leadership”, “transform leader”. Searching the Scopus database for transformational leadership titles, abstracts, and author key words yielded a total of 12,874 entries. Prior to processing the analysis, the author keywords were re-labeled by making a thesaurus file. The current study has used PRISMA (Preferred reporting items for systematic reviews and meta- analyses) guidelines and procedures. This study also focused on how the researches have been continuously progressing on transformational leadership. Its goal is to make this topic’s research more visible by showcasing its present features and providing a thorough and retrospective evaluation of publications. The study used VosViewer to analyze the collected data.